Integration of E-Service Quality (E-Servqual) And Importance Performance Analysis (IPA) Methods on BTN Mobile Application User Satisfaction: Integrasi Metode E-Service Quality (E-Servqual) dan Importance Performance Analysis (IPA) Terhadap Kepuasan Pengguna Aplikasi BTN Mobile - Agustina, Deva; Suyatno, Dwi Fatrianto (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2024)
Bank Tabungan Negara (BTN) is one of the banks that provide mobile banking services, namely BTN Mobile, which answers the needs of Bank BTN customers to conduct banking or financial transactions digitally using only their smartphones. Currently BTN Mobile has developed by providing various services to facilitate customers in digital transactions such as interbank transfers, top-up digital wallets, payment via QR, cash withdrawals without using ATMs, and so on. This study aims to measure the level of satisfaction of BTN Mobile application users using the E-Servqual and Importance Performance Analysis (IPA) methods. From distributing questionnaires, data was obtained from 173 respondents who used the BTN Mobile application in the general public. From the results of the study, it was found that the level of satisfaction based on the gap analysis results obtained an average gap value of -0.28 which indicates that the quality of the BTN Mobile application currently does not meet users' expectations. The level of user satisfaction based on the customer satisfaction index (CSI) is 80%, which means that users are very satisfied with the BTN Mobile application. Then the indicators that need improvement in quadrant I of the IPA method are indicators, B3 (Fulfillment), C6 (System Availability), and D2 (Responsiveness). Recommendations for improvement include providing easy and accurate transaction services, features for purchasing credit, data, and top-ups, as well as a quick response if there is a problem with the customer's account.